Dysregulation of the endomembrane homeostasis triggers vascular smooth muscle cell phenotype switching. (10th June 2022) - Hense, N; Mir, B; Marx, N; Goettsch, C
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft Background: Cardiovascular diseases are a leading cause of mortality globally, with cardiovascular calcification as a prominent predictor and contributor. Notably, microcalcifications might cause atherosclerotic plaque rupture, leading to myocardial infarction. Calcified plaque remodeling accompanies phenotypic modulation of vascular smooth muscle cells (SMCs). Previously, we showed that extracellular vesicles (EVs) released from calcifying SMCs are pivotal for microcalcification formation. EVs originate from the endolysosomal system. The lipid kinase FYVE-type zinc finger containing phosphoinositide kinase (PIKfyve) plays a role in the endolysosomal maturation. Here, we investigated how modulation of the endolysosomal system intersects with SMC phenotype regulation. Methods and Results: In calcified arteries and SMCs, we observed increased PIKfyve expression. Inhibition of PIKfyve with the small molecule Apilimod inhibited osteogenic differentiation of SMCs in an in vitro calcification model. Apilimod reduced tissue non-specific alkaline phosphatase (TNAP) – an early marker of SMC calcification on mRNA (-79%, p<0.01), protein (-96%, p<0.01) and activity (-92%, p<0.01) levels. Additionally, matrix mineralization and collagen network formation are inhibited. SMC-secreted EVs exhibited a lower mineral content and reduced aggregation potential assessed by osteosense-based flow cytometry and turbidity assays. Transcriptome analyses revealed that the anti-calcifying effect is accompanied by a decreased expression of contractile SMC genes. Validation by RT-PCR supported that SMC-specific markers (ACTA2, SM22) and the key SMC transcription factor MYOCD were downregulated, while the expression of macrophage-like SMC markers (LGALS3, CD68) was induced. On the other hand, Apilimod increased the expression of adipogenic transcription factors (CEBPA, PPARG) and genes of the cholesterol and fatty acid metabolism pathways (SREBF2, HMGCR, FABP3, CD36) and induced the nuclear translocation of PPARγ, the main regulator of adipogenic differentiation. Fluorescence-based assays revealed increased fatty acid and disrupted low-density lipoprotein (LDL) uptake in Apilimod-treated SMCs. In Ldlr-deficient mice fed a high-fat, high-cholesterol diet for 15 weeks and treated with Apilimod for 5 weeks, we found differentially distributed plaque lipid depositions detected by Oil Red O staining. Conclusion: Disrupting the endolysosomal maturation by PIKfyve inhibition ameliorates SMC calcification and induces a phenotypic adipogenic-like, pro-inflammatory adaption. Our data elucidates the importance of SMC phenotype monitoring during therapeutic interference. The exact lineage characteristics of these SMCs remain to be further investigated.